Exploring the Influence of Training Factors on Job Performance in the Qatari Governmental Sector: The Mediating Role of Leadership Skills - Saeed, Wedad Fadhul Saleh Ahmed; El-Gohary , Hatem (Journal of Ecohumanism, 2024)
This study examines the impact of training-related factors on employees’ job performance in Qatar, focusing on the role of acquired leadership skills as a mediating variable. It considers training-related factors as the independent variable, employees’ job performance as the dependent variable, and acquired leadership skills as the mediating factor. The study sample includes 332 experienced employees from the government sector. A positivist approach was used, employing a questionnaire to collect quantitative data and reviewing previous studies for qualitative analysis. This methodology provided a structured understanding of the relationship between training, leadership development, and job performance. The findings highlight the importance of the training environment in shaping trainees’ commitment to the programme. The trainer’s expertise and knowledge of the training material play a role in building trainees’ confidence. Training content influences the development of employees’ skills and knowledge, reinforcing the need for active employee engagement in the training process. The study recommends discussing employees’ training needs to ensure programmes align with their job roles, revising training schedules to improve participation, especially for fieldwork employees, conducting follow-ups to assess training effectiveness, and designing training programmes to enhance job performance.